NIR-II phototherapy agents with aggregation-induced emission characteristics for tumor imaging and therapy. (June 2022) - Shi, Tingyu; Huang, Chenchen; Li, Yang; Huang, Feihe; Yin, Shouchun
Abstract: As one of the major public health concerns, malignant tumors threaten people's lives. With the increasing demand for early accurate diagnosis and the safe treatment of tumors, non-invasive optical imaging (including fluorescence imaging and photoacoustic imaging) and phototherapy (including photothermal therapy and photodynamic therapy) have received much attention. In particular, light in the near-infrared second region (NIR-II) has been attracting research interest, owing to its deep penetration, minimal tissue autofluorescence, and decreased tissue absorption and scattering. Among all biological materials, organic nanomaterials with aggregation-induced emission (AIE) properties have attracted significant attention, owing to various incomparable advantages, such as high brightness, good photostability, tunable photophysical properties, and good biosafety. To modulate the working optical region of AIE molecules to the NIR-II region, many researchers have tried a variety of methods in recent years, and the focus of this review is to summarize the three most common methods from the perspective of molecular design strategies. In addition, this article briefly reviews the recent five-year progress of NIR-II AIE luminophores in tumor imaging and phototherapy applications. The research status is also summarized and prospected, with the hope of contributing to further research.